Evaluation of the Effect of Gene Duplication by Genome Editing on Drug Resistance in Plasmodium falciparum - Kubota, Rie; Ishino, Tomoko; Iwanaga, Shiroh; Shinzawa, Naoaki (Frontiers in Cellular and Infection Microbiology, 2022)
The emergence and spread of drug resistant Plasmodium falciparum has compromised antimalarial efficacy and threatens the global malaria elimination campaign using artemisinin combination therapies. The impacts of amino acid substitutions in antimalarial drug resistance-associated genes on drug susceptibility have been investigated; however, the effects of amplification of those genes remain unexplored due to the lack of robust genetic approaches. Here, we generated transgenic P. falciparum parasites with an additional copy of a drug resistance-associated gene using the highly efficient CRISPR/Cas9 system and investigated their drug response. Insertion of a drug resistance-associated gene expression cassette in the genome resulted in a roughly two-fold increase of mRNA levels of the target gene mdr1, which encodes multidrug resistance protein 1. The gene duplication event contributed to resistance to mefloquine, lumefantrine, and dihydroartemisinin; while the duplication of a genomic region encoding plasmepsin 2 and plasmepsin 3 did not affect resistance to antimalarial drugs, including piperaquine. We further demonstrated that mdr1 mRNA expression levels are strongly associated with mefloquine resistance in several field-derived P. falciparum lines with various genetic backgrounds. This study provides compelling evidence that mdr1 could serve as a molecular marker for the surveillance of mefloquine resistant parasites. Long DNA integration into parasite genomes using the CRISPR/Cas9 system provides a useful tool for the evaluation of the effect of copy number variation on drug response.